Salmonella enterica serovar Schwarzengrund: Distribution, Virulence, and Antimicrobial Resistance - Monique A. Felix; Jing Han; Bijay K. Khajanchi; Yasser M. Sanad; Shaohua Zhao; Steven L. Foley (Microorganisms)
The global incidence of Salmonella enterica serovar Schwarzengrund has risen in recent years. This serotype has been isolated from poultry, retail meat, and other food products, leading to multiple outbreaks. Alongside the increase in infections, there are growing concerns about the increasing levels of antimicrobial resistance (AMR) among S. Schwarzengrund strains. This study aims to better understand the genetic factors possibly contributing to the rising prevalence of S. Schwarzengrund by analyzing the sequences of 2058 isolates from both human patients (N = 313) and food- and animal-associated sources, including chicken (N = 1145), turkey (N = 300), pork (N = 132), and other sources (N = 168). Data were obtained from GenBank and analyzed for AMR genes using AMRFinder. Additionally, putative virulence genes and plasmid transfer genes were assessed using the Virulence and AMR Plasmid Transfer Factor Database. AMR genes were found in 1269 (61.7%) of the isolates, with a total of 2478 AMR genes among the isolates, the most common being aph(3″)-Ib (N = 969, 47.1%), tet(A) (N = 190, 9.2%), and sul2 (N = 150, 7.3%), which are responsible for resistance to aminoglycoside, tetracycline, and sulfonamide, respectively. Additionally, 1060 (51.5%) isolates carried multiple plasmid transfer genes associated with IncFIB-FIC(FII) plasmids. Other plasmid types found in at least 1% of the strains included IncI1 (N = 101, 4.9%), IncHI2 (N = 62, 3.0%), or IncHI1 (N = 24, 1.2%). The virulence gene profiles of human isolates showed diversity but largely overlapped with those from different food sources. Notably, the aerobactin iron acquisition genes, associated with Salmonella’s virulence and colonization, were highly prevalent among chicken isolates (N = 1019, 89.0%) but less frequent in isolates from other sources (N = 65, 7.2%). IncFIB-FIC(FII) plasmids, commonly harboring the aerobactin operon, were highly prevalent among chicken-related isolates and present in about 10% of human isolates. The diverse plasmid, AMR, and virulence gene profiles in human-associated isolates suggest that multiple factors may contribute to the increased virulence in S. Schwarzengrund.